Along the Mohawk Trail; Or, Boy Scouts on Lake Champlain - Fitzhugh, Percy Keese, 1876-1950; West, James E. (James Edward), 1876-1948; Schuyler, Remington, 1884-1955 (Salt Lake City, UT : Project Gutenberg, 2019)
"Along the Mohawk Trail; Or, Boy Scouts on Lake Champlain" by Percy Keese Fitzhugh is a children's adventure novel written in the early 20th century. The story centers around Gordon Lord, a young scout who sets out to find his troop, which is camping somewhere along Lake Champlain. The narrative captures the spirit of scouting and the importance of adventure, camaraderie, and resourcefulness in the lives of boys exploring the outdoors. The opening portion of the book introduces Gordon as he sets off for a summer camping trip but misses the train due to his distraction while helping a former teacher. After some initial flurry, he eventually decides to embark on a quest to locate his troop. As Gordon navigates through the woods, he discovers clues indicating that his fellow scouts have recently passed through the area, including an arrow marked in pink chalk and signs of disturbance near a river. His determination leads him to the realization that adventure awaits, as he pushes onward to find his friends while encountering various challenges and showcasing his keen scouting skills. (This is an automatically generated summary.)
Release date is 2019-09-09
E-text prepared by Roger Frank and Sue Clark from page images digitized by the Google Books Library Project (http://books.google.com) and generously made available by HathiTrust Digital Library (https://www.hathitrust.org/)
Keywords: Camping -- Juvenile fiction; Boy Scouts of America -- Juvenile fiction; Travel -- Juvenile fiction; Outdoor life -- Juvenile fiction; New York (State) -- Juvenile fiction